Gemcitabine plus Nab-paclitaxel as a second-line treatment following FOLFIRINOX failure in advanced pancreatic cancer: a multicenter, single-arm, open-label, phase 2 trial - Gunn Huh (SAGE Publishing, 2021)
Background: The aim of this study was to evaluate the efficacy and safety of gemcitabine plus nab-paclitaxel (GnP) as second-line chemotherapy following first-line FOLFIRINOX treatment failure in advanced pancreatic cancer. Methods: This was a multicenter, single-arm, open-label, phase 2 trial done at three tertiary centers in South Korea from May 2018 to December 2019. Eligible patients were aged 20 years or older, had histologically confirmed advanced pancreatic ductal adenocarcinoma, and disease progression after receiving first-line FOLFIRINOX. Patients received a second-line GnP regimen as intravenous nab-paclitaxel at a dose of 125 mg/m 2 and gemcitabine at a dose of 1000 mg/m 2 , on days 1, 8, and 15 every 4 weeks until disease progression or unacceptable toxicity. The primary outcome was survival rate at 6 months and the secondary outcomes were median progression-free survival (PFS), overall survival (OS), disease control rate (DCR), and adverse events. This study is registered with Clinicaltrials.gov. (NCT03401827) Results: Forty patients were enrolled in the study. The survival rate at 6 months was 72.5% [95% confidence interval (CI), 59.9–87.7], achieving superiority over prespecified assumed 6-month OS rate of 20% for best supportive care only ( p  < 0.001). The median PFS and OS were 5.8 months (95% CI, 4.3–8.7) and 9.9 months (95% CI, 7.5–12.4), respectively. DCR was 87.5% with six partial responses and 29 stable diseases. Grade 3 or higher treatment-related adverse events occurred in 25 (62.5%) patients with the most common being thrombocytopenia, anemia, neutropenia, peripheral neuropathy, and peripheral edema. Conclusion: GnP demonstrated favorable efficacy with acceptable toxicity in patients with advanced pancreatic ductal adenocarcinoma after FOLFIRINOX failure.